2010
DOI: 10.1038/bmt.2010.52
|View full text |Cite
|
Sign up to set email alerts
|

Observational prospective study of viral infections in children undergoing allogeneic hematopoietic cell transplantation: a 3-year GETMON experience

Abstract: We studied surveillance, incidence and outcome of viral infections in children undergoing allogeneic hematopoietic cell transplantation (HCT) in the main pediatric transplant units in Spain. We prospectively collected data from first year post-HCT in every consecutive allogeneic HCT performed during 3 years (N ¼ 215): first HCT ¼ 188 and second HCT ¼ 27; median age ¼ 6.6 years (0.1-20.7). Most patients had acute leukemia (N ¼ 137) and 135 recipients (63%) were CMV seropositive. A total of 46 patients underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 21 publications
3
40
2
Order By: Relevance
“…Of note, 61.8% of our patients tested positive for viral DNA at least once, similar to other reports (Schonberger et al, 2010; Verdeguer et al, 2011). In agreement with most of the reviewed literature, CMV represents the most frequent virus detected in transplanted patients (Comoli and Ginevri, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of note, 61.8% of our patients tested positive for viral DNA at least once, similar to other reports (Schonberger et al, 2010; Verdeguer et al, 2011). In agreement with most of the reviewed literature, CMV represents the most frequent virus detected in transplanted patients (Comoli and Ginevri, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…They reported an overall detection of any viral DNA in 62.5% of the recipients, with CMV being detected in the serum of 28% of patients while HHV6, ADV and BKV were less frequently detected (Schonberger et al, 2010). Another study performed in Spain, also identified CMV as the most frequent virus (28.9%) among the plasma analyzed (Verdeguer et al, 2011). …”
Section: Discussionmentioning
confidence: 88%
“…Our cTCR/TCD protocol involved ATG, which has been commonly used to deplete T cells in vivo, prevent rejection and GvHD [37,38], and is known to cause prolonged lymphopenia through widespread depletion of lymphocytes, thus elevating the risk for infection [31]. In particular, ATG has a strong impact on the CD4+ T-cell compartment, leading to low CD4+ T-cell counts and low CD4+/CD8+ T-cell ratios [39].…”
Section: Discussionmentioning
confidence: 99%
“…For other viruses, no clear differences between both groups could be observed. Improved control of herpesvirus in the TCR/ PTCY cohort showed association with a fast recovery of total The high overall incidence of detectable viral infections in our patient cohort (84 %) is consistent with reported data of GvHD graft-versus-host disease, NRM nonrelapse mortality, aGvHD acute graft-versus-host disease, cGvHD chronic graft-versus-host disease, IPS interstitial pneumonitis syndrome OS overall survival, vs versus, AML acute myeloid leukemia, ALL acute lymphoblastic leukemia, CR complete remission, CRi complete remission with incomplete platelet recovery, MAC myeloablative conditioning, RIC reduced intensity conditioning, TCR/PTCY T-cell-replete and high-dose cyclophosphamide posttransplantation, cTCR/TCD combined T-cell-replete and T-cell-deplete, GvHD graft-versus-host disease transplantation from alternative donors, such as umbilical cord blood (UCB) or HLA-mismatched unrelated donor-derived transplantation [5,9,[29][30][31][32]. However, when we separately consider our TCR/PTCY-transplanted cohort, we found an incidence of virus infection that is close to the reported incidence in HLA-matched transplantation [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Some viral infections, including CMV, BKV, EBV, AdV and HHV6 are frequent and endemic, while others are seasonal (e.g. influenza, parainfluenza, and respiratory syncytial virus) but all can contribute to substantial transplant-associated disease or death(2022). This broad spectrum of problematic viruses makes it impracticable to develop products for a single virus in a single patient.…”
Section: Discussionmentioning
confidence: 99%